ESTIMASI NILAI WAJAR EKUITAS PT SEMEN BATURAJA (PERSERO) DALAM RANGKA PRIVATISASI TAHUN 2011 - , Nurbiyanto, Prof. Dr. Eduardus Tandelilin, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to estimate the fair value of PT Semen Baturaja (Persero) equity at year end 2010 pursuing to the governmentâs privatization plan. The used of various methods in equity fair value estimation could serve as a basis in determining the fair market value of privatizing the above mentioned company. It is important that this research is to be carried out as it occurs in several privatization cases of a state-owned corporation were sold at low price resulting to governmentsâ lost. Data examined were the companyâs financial statement, financial statements of comparable company, stock prices of comparable company and Jakarta Composite Index. The methods used to estimate the equity fair value are (1) free cash flow to equity discount models